Evolutions of stress and microstructure in multilayer ferroelectric actuators under different temperature environments. Issue 12 (1st December 2016) - Huang, Cheng; Gao, Cun-Fa
ABSTRACT: The multilayer ferroelectric actuator (MFA) with electrodes is an important smart structure and it has found wide application in engineering. Under the applied electric–elastic loads, the local stress concentration will be intensified near the tips of electrodes, and it finally may lead to the failure of the MFA. On the other hand, the temperature-dependent behavior of ferroelectrics results in the novel evolutions of local stresses and microstructure in the MFA under different temperature environments. In this work, the different temperature-induced nonlinear behavior and electroelastic field concentration around the electrode tip in the MFA is studied based on a phase-field approach containing the time-dependent Ginzburg–Landau equation. Using three-dimensional nonlinear finite element method, the temperature-induced domain switching behavior of the MFA and the evolution of the local stress near the electrode tips are simulated under different loadings and temperatures. It is found that the maximum tensile stress ahead of the electrode tip increases as the temperature increases from room temperature to a critical temperature. However, over the critical temperature, the stress decreases significantly due to the ferroelectric–paraelectric phase transition, which implies that by optimizing the environmental temperature, the local stress concentrations can be controlled.